Stress distribution in a composite material with a row of antiphase periodically curved fibers - Akbarov, S. D.; Kosker, R.; Ucan, Y. (CONSULTANTS BUREAU/SPRINGER, 2006)
The stress distribution in an infinite matrix containing a row of antiphase periodically curved fibers is studied using the piecewise-homogeneous body model and the exact three-dimensional equations of elasticity theory for anisotropic bodies. It is assumed that the midlines of the fibers are located in the same plane and the materials of the fibers are the same. Numerical results are presented for the case where the materials of the fibers and matrix are isotropic and homogeneous.
Keywords: unidirectional fibrous composite; row of fibers; self-balanced stresses; curved fibers; ELASTIC BODY; MECHANICS; MATRIX